LEARNER STUDENT IN DISTANCE LEARNING: COURSEWARE AND EVALUATION - Martins, Evaneide Dourado (2017)
This paper aims to show the learning behavior in the face-to-face teaching and the teacher’s perceiving about their lessons. Just as there is a concern to use innovative, motivating and creative didactics in the face-to-face teaching, it happens in distance teaching, as well. The logic behind this research is the consideration of students separated of teacher, but still having the courseware with them. However the point is the good crafting of courseware, aiming quality, plainness, objectivity and easiness to understand, which makes the courseware to be used as a guide for the student to get the knowledge in a satisfactory way and become a critic citizen. Educational institutions use several ways of evaluation whether in face-to-face or distance learning, but the type of used evaluations is presented and how each of them contribute to teaching-learning